2016
DOI: 10.3329/jbau.v13i2.28771
|View full text |Cite
|
Sign up to set email alerts
|

Quality of some hybrid seeds of rice and control of seed borne fungi in Bangladesh

Abstract: A study was conducted for assessing quality of 15 hybrid rice seed samples and management of seed borne fungal pathogens by three selected chemicals namely Bavistin (0.3%), Thiovit (0.3%) and Provax (0.3%) along with two botanicals such as: Garlic extract (Allium sativum) (1:1) and Allamanda leaf extract (Allamanda cathartica) (1:1) and a bio-control agent BAU-Biofungicide @ 3% (Trichoderma based preparation) at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Microbial activities also grow with increasing the values of moisture content and increase the losses of quality (Ruska and Timar 2010). These results were consistent with the findings of Akter et al (2015). Seeds stored in PICS bag and super grain bag retained the highest seed germination for a longer time (Khatri et al 2019) than other tested seed storage materials.…”
Section: Seed Germination Percentagesupporting
confidence: 88%
“…Microbial activities also grow with increasing the values of moisture content and increase the losses of quality (Ruska and Timar 2010). These results were consistent with the findings of Akter et al (2015). Seeds stored in PICS bag and super grain bag retained the highest seed germination for a longer time (Khatri et al 2019) than other tested seed storage materials.…”
Section: Seed Germination Percentagesupporting
confidence: 88%
“…There is a lot of evidence in Bangladesh that farmers quit hybrid rice cultivation due to the high rate of failure of germination of the seeds when planted (Pervez 2018). Research brought out the seed quality of 15 hybrid rice seed suppliers, with seeds from different companies, and showed that only 37.7 to 85.7 % of seeds were healthy (Akter and Hossain 2015).…”
Section: Massive Germination Failure Of Purchased Hybrid Rice Seedsmentioning
confidence: 99%
“…The production and supply of quality seed in rice plays a vital role to meet the growing population. It has been shown experimentally that only by using good quality healthy seed, rice yield could be increased by 10-15% (Akter et al, 2015). In rice, there is no much problem in seed storage if the crop is well maintained during production period.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant substances like ascorbic acid, tocopherol and glutathione had a positive effect on the seedling vigour (Basra et al, 2006;Draganic and Lekic, 2012). Similarly, seed treatment with biofungicide has been found as superior in increasing germination and vigour in rice seeds (Akter and Hossain, 2015). Therefore, an experiment was conducted in the rice variety ADT (R) 46 seeds by treating with different antioxidants as to manage its poor storage behavior.…”
Section: Introductionmentioning
confidence: 99%